Ocimun basilicum L., nuevo hospedante en Cuba de pseudomonas cichorii - Soto, W.R.=700 1 Lopez, M.; Gonzalez, J.; Oliva, P.; Dueñas, M.
(Es, En)
Ilus., 17 ref.
Keywords: OCIMUN BASILICUM; PSEUDOMONAS CICHORII; ETIOLOGIA; EPIDEMIOLOGIA; CUBA; ALBAHACA